POLICY DEVELOPMENT TRAINING AND EDUCATION RESOURCES TO REFORM THE LOCAL GOVERNMENT DISTRICT OF MAKASSAR SIDENRENG RAPPANG - Maldun, Syamsuddin (Journal of Humanity, 2015)
This research aims to know and study the strategy of resource development policy reform of local government district of Makassar Sidenreng Rappang. The research method used is descriptive qualitative study type, while the phenomenological approach is used. This is intended to give description in a systematic, factual and actual response object is examined. Results of the research implementation of education and training is not conducted in a planned and timely to get quality apparatus of the abilities, knowledge, skills, expertise, and job skills, as well as a good mental attitude, and optimal performance. Whereas in the era of regional autonomy, it takes the resources of local government apparatus that is intelligent and responsive to the needs of an increasingly complex society services.Â